Sense and meanings of basic and intermediate academic teachers about the question Why do you ask the student questions during the class? (Quaestiones Disputatae: temas en debate, 2020)
The research is focused on knowing, from the inclusive critical approach of pedagogy, what is the meaning and significance that teachers in the municipality of Chimá-Córdoba in Colombia have about the question: Why do you ask the student questions during class? The questions that teachers ask in class or outside it in an educational institution have a meaning and significance for every teacher, which is a way of developing thinking in the classroom. The pedagogy of the question and its practice allows the teacher to find situations that indicate to him/her the state in which the students are. The reflection made on the students' previous interests when being questioned through the pedagogical question can have a problematic, open, inquiring, reflexive, technical, and/or any other connotation that provides the teacher with a diagnosis on the level of learning and the development of critical thinking; furthermore, to know how the consultations, and/or the process of axiological formation are going. The methodology was approached from the qualitative design inspired by the interpretative paradigm or vertehen, of the narrative-interpretative type. An intentional sample was used, with the aim of being able to move towards a deliberate sampling throughout the study, based on the information needs detected in the first results. Among the findings, it was found that teachers apply a greater percentage of traditional conceptions of self and heterostructuralist teaching than from a socio-cognitivist perspective.
Keywords: Suidagogy; pedagogical question; pedagogy; praxis; teachers; critical thinking; teaching; learning